2010
DOI: 10.1007/s00339-010-5784-z
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of nuclear reactions under laser irradiation of Au nanoparticles in the aqueous solution of Uranium salt

Abstract: Laser exposure of suspension of either gold or palladium nanoparticles in aqueous solutions of UO 2 Cl 2 of natural isotope abundance was experimentally studied. Picosecond Nd:YAG lasers at peak power of 10 11 -10 13 W/cm 2 at the wavelength of 1.06 -0.355 m were used as well as a visible-range Cu vapor laser at peak power of 10 10 W/cm 2 . The composition of colloidal solutions before and after laser exposure was analyzed using atomic absorption and gamma spectroscopy in 0.06 -1 MeV range of photon energy. A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…However, the reproducible results from experimen tal studies of nuclear transformations of the above type under conditions of the low temperature plasma formed in near surface regions of metal upon the laser ablation of metals in aqueous media [7][8][9][10][11][12][13][14][15] provide grounds for continuing the search for adequate mech anisms of cold nuclear fusion, especially since the ori gins of this problem can be attributed to the pioneering studies of the 1950s by Artsimovich and colleagues on powerful electric discharges in tubes containing deute rium-inert gas mixtures [16,17]. It was found that short pulses of neutrons and hard X rays with energies of 300-400 keV concurrently generated in the middle region of the discharge tubes at a deuterium partial pressure of up to several tens of Torr, and the applied voltages of several tens of kV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the reproducible results from experimen tal studies of nuclear transformations of the above type under conditions of the low temperature plasma formed in near surface regions of metal upon the laser ablation of metals in aqueous media [7][8][9][10][11][12][13][14][15] provide grounds for continuing the search for adequate mech anisms of cold nuclear fusion, especially since the ori gins of this problem can be attributed to the pioneering studies of the 1950s by Artsimovich and colleagues on powerful electric discharges in tubes containing deute rium-inert gas mixtures [16,17]. It was found that short pulses of neutrons and hard X rays with energies of 300-400 keV concurrently generated in the middle region of the discharge tubes at a deuterium partial pressure of up to several tens of Torr, and the applied voltages of several tens of kV.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work it is shown that along with the results of [16,17], the totality of the experimental results in works [7][8][9][10][11][12][13][14][15] on the initiation of a variety of nuclear transformations under conditions of the laser ablation of metals in aqueous media can be under stood within the concepts of interaction between high energy (on the chemical scale) electrons and nuclei, leading to the possibility of changes in the state of nuclear matter with a transition from the standard (described as an ensemble of interacting nucleons) to an unbalanced nonstationary state with an "inner shake up" or "in shake up" state of nuclear matter [21], for which the concept of the nucleus as a collec tion of nucleons becomes meaningless.…”
Section: Introductionmentioning
confidence: 99%
“…The irradiation of a solution of uranyl chloride with beryllium nanoparticles accelerates both the beta- ( 234 Th, 234m Pa) and alpha-decay ( 235 U) of nuclides. A change in the uranium-235 activity under laser irradiation of gold nanoparticles in an aqueous solution of uranyl chloride was observed only when using a femtosecond Ti:sapphire laser [16], while the irradiation of the same solution by a picosecond laser did not change the uranium-235 activity within the measurement error [15].…”
Section: Discussionmentioning
confidence: 90%
“…In recent works, it was shown that laser irradiation of metal nanoparticles in aqueous solutions of salts of radioactive isotopes considerably shifts their activity from equilibrium values [15,16]. The change in the gamma activity of uranium series nuclides is caused by acceleration of their fission under action of laser radiation.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that laser irradiation of nanoparticles of metals in aqueous solutions of salts of uranium leads to a significant deviation of activity of the radionuclides of this family from the equilibrium values [5,6]. Change of activity of radionuclides occurs in the process of laser irradiation of metal targets in aqueous solutions of salts of uranium.…”
Section: Laser Ablation Of Gold Nanoparticles In Solutions Of Salts Umentioning
confidence: 99%